Optimizing the Utilization of Local Government Assets in Gorontalo District - Potale, Marlen; Saprudin, Saprudin; Masiaga, Novaliastuti; Yakup, Yakup (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This study aims to analyze the management of Regional Owned Assets by the Gorontalo District Government, focusing on optimizing the utilization of BMD to increase Regional Original Revenue. The study evaluates BMD management practices in Gorontalo District from 2018 to 2022 using qualitative methods through interviews, observations, and documentation. The results show that BMD management includes inventory, appraisal, and legal audits to ensure effective asset utilization. Schemes such as leasing and lending have significantly contributed to Regional Original Revenue. Although revenue from BMD is fluctuating, optimization efforts are ongoing. Challenges include asset maintenance for maximum results. The implications of this study highlight the importance of strict supervision and the application of good state financial management principles for efficient and sustainable BMD management.